Certain Indefinite Integrals Involving Laguerre Polynomials (Global Journal of Science Frontier Research, 2012)
In this paper we have established certain indefinite integrals involving Polylogarithm and Laguerre Polynomials. The results represent here are assume to be new.
Keywords: Polylogarithm; Laguerre polynomials; Gaussian Hypergeometric Function